Szacowanie stopy dyskontowej w rachunku efektywności projektów inwestycyjnych - wybrane problem - Szóstek, Aneta (Appraisal of Discount Rate in Calculation of Investment Projects Effectiveness - Selected Problems, 2006)
A correct evaluation of investment project efficiency is an essential factor of rational investment I taisions. Discount rate has a fundamental importance in calculation of investment effectiveness. It I makes cash flows be comparable in consecutive periods of investment duration. A level of discount I rate should ensure investors a compensation for a postponement of current consumption, cover for posts of involved capital (private and foreign) and risk bonus. The article focuses on the idea of I correct evaluation of discount rate in calculation of investment project effectiveness. The difficulty [lies mainly in application of theoretical methods in practice. This problem has been bothering scientists and practitioners for years and it has not found a satisfying solution yet.(
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 623-635